Targeted Literature Review of the Burden of Respiratory Syncytial Infection among High-Risk and Elderly Patients in Asia Pacific Region - Daisuke Kurai; JoonYoung Song; Yhu-Chering Huang; Zhijun Jie; Petar Atanasov; Xiaobin Jiang; Luis Hernandez-Pastor; Tom Hsun-Wei Huang; SeongBeom Park; KyungHwa Lim; Peter C. Richmond (Infectious Diseases and Therapy, 2023)
Abstract Introduction The burden of respiratory syncytial virus (RSV), which causes acute respiratory illness, is well recognized among the pediatric population but also imposes a significant risk to the elderly (age ≥ 60) and those with underlying comorbidities. The study aimed to review the most recent data on epidemiology and burden (clinical and economic) of RSV in the elderly/high-risk populations in China, Japan, South Korea, Taiwan, and Australia. Methods A targeted review was conducted of English, Japanese, Korean, and Chinese language articles published from 1 January 2010 to 7 October 2020 relevant for the purpose. Results A total of 881 studies were identified, and 41 were included. The median proportion of elderly patients with RSV in all adult patients with acute respiratory infection (ARI) or community acquired pneumonia was 79.78% (71.43–88.12%) in Japan, 48.00% (3.64–80.00%) in China, 41.67% (33.33–50.00%) in Taiwan, 38.61% in Australia, and 28.57% (22.76–33.33%) in South Korea. RSV was associated with a high clinical burden on those patients with comorbidities such as asthma and chronic obstructive pulmonary disease. In China, inpatients with ARI showed a significantly higher rate of RSV-related hospitalization than outpatients (13.22% versus 4.08%, p < 0.01). The median length of hospital stay among elderly patients with RSV was longest in Japan (30 days) and shortest in China (7 days). Mortality data varied by region with some studies reporting rates as high as 12.00% (9/75) in hospitalized elderly patients. Finally, data on the economic burden was only available for South Korea, with the median cost of a medical admission for an elderly patient with RSV being US dollar (USD) 2933. Conclusion RSV infection is a major source of disease burden among elderly patients, especially in regions with aging populations. It also complicates the management of those with underlying diseases. Appropriate prevention strategies are required to reduce the burden among the adult, especially the elderly, population. Data gaps regarding economic burden of RSV infection in the Asia Pacific region indicates the need for further research to increase our understanding on the burden of this disease in this region.